2008
DOI: 10.1002/mrm.21642
|View full text |Cite
|
Sign up to set email alerts
|

Serial in vivo positive contrast MRI of iron oxide‐labeled embryonic stem cell‐derived cardiac precursor cells in a mouse model of myocardial infarction

Abstract: Myocardial regeneration with stem-cell transplantation is a possible treatment option to reverse deleterious effects that occur after myocardial infarction. Since little is known about stem cell survival after transplantation, developing techniques for "tracking" cells would be desirable. Iron-oxide-labeled stem cells have been used for in vivo tracking using MRI but produce negative contrast images that are difficult to interpret. The aim of the current study was to test a positive contrast MR technique using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 37 publications
3
55
0
Order By: Relevance
“…Recently methods of tracking cells, using MRI or optical imaging methods, have been shown to be possible in settings such as heart attacks and stroke [22,62,113]. This holds much promise for evaluating where injected cells end up residing which will be particularly important for assessing the validity of cell-based treatments.…”
Section: How Do We Assess Success?mentioning
confidence: 99%
“…Recently methods of tracking cells, using MRI or optical imaging methods, have been shown to be possible in settings such as heart attacks and stroke [22,62,113]. This holds much promise for evaluating where injected cells end up residing which will be particularly important for assessing the validity of cell-based treatments.…”
Section: How Do We Assess Success?mentioning
confidence: 99%
“…EMT is observed routinely in developmental processes, but is also believed to play an important role in the migration, invasion, and metastasis of various cancers (6)(7)(8)(9). It also promotes the generation of cancer stem cells, thereby contributing to tumor recurrence and metastasis (10,11). Two recent publications have challenged this dogma for breast and pancreatic cancers and have suggested instead that EMT confers chemoresistance rather than metastatic potential to tumor cells (12,13).…”
mentioning
confidence: 99%
“…Recent studies, however, have shown that iron oxide labeling, combined with magnetic targeting, might improve graft retention in the rat heart [29,30,34,36]. Thus, ferumoxytol cell labeling might have utility in both in vivo cardiac graft imaging and cell retention.…”
Section: Mri Of Labeled Hesc-cpcs In the Pig Heart ©Alphamed Press 2016mentioning
confidence: 99%
“…Recent studies have described the properties of the ultra-small superparamagnetic iron oxide nanoparticle, ferumoxytol (Feraheme; AMAG Pharmaceuticals, Inc., Waltham, MA, http://www.amagpharma.com) as a labeling agent [7,14,[29][30][31]. Ferumoxytol interacts with cells via a synthetic carbohydrate coating and is currently used for the treatment of iron-deficiency anemia in the presence of chronic kidney disease [32].…”
Section: Introductionmentioning
confidence: 99%